GOOD LOCAL GOVERNANCE MELALUI PENINGKATAN KUALITAS PELAYANAN PUBLIK - Tiwi Rizkiyani (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The change in the paradigm from government to governance has changed the order of government management, including in Indonesia. The governance paradigm transforms traditional governance into modern governance. The government is not the only actor in governance, but there is a synergistic relationship with other sectors in order to realize good governance. Governance involves government partnerships in carrying out government functions with the private sector and also the community. Strengthening synergistic and harmonious relations between the government, private sector, and the community is expected to improve the performance of the public sector so that good governance can be realized. The existence of decentralization in the form of regional autonomy in Indonesia is expected to help the central government in realizing good governance in the regions. Good local governance or good governance at the regional level, one of which focuses on improving the quality of public services. Local governments responsible for providing public services to the community effectively and efficiently. This article will explain how good local governance through improving the quality of public services in the regions. The method used is the study of literature. The way to realize good local governance through improving the quality of public services in the regions is to carry out consistent and sustainable public service reforms. Keywords: Good governance; Local government; Public services.